The effects of Sixteen weeks of selected aerobic training on Serum osteopontin and osteocalcin in sedentary middle-aged women - هاجر عباس زاده صورتی; خسرو ابراهیم; حجت الله نیک بخت (فیزیولوژی ورزش و فعالیت بدنی)
Purpose: The aim of this study was to examine the effects of 16-weeks selective aerobic training on serum osteopontin and osteocalcin in sedentary middle-aged women. Methods: In this semi-experimental study. 16 sedentary middle-aged women (39٫375+3٫667 years) who had no regular physical activity were non-randomly selected as the subjects, randomly divided into experimental (n=9) and control groups (n=7). Fasting blood samples were taken before and after 16 weeks of aerobic training. Aerobic training was performed at an intensity corresponding to 65% to 70% of the subjects' target heart rate for 3 d٫wk and for 16 weeks. Paired t-test was used to determine the differences between before and after training data in each group, and Mann-Whitney test was used to compare data in training and control groups. Statistical significance was set at o≤ 0.05. Results: osteopontin and osteocalcin increased significantly in the experimental group than in the control group after 16 weeks of aerobic training (respectively, p=0٫023 and p=0٫021). In the within-group comparisons, the training group in both indices showed a significant increase (p<0٫05). However, the control group showed no significant changes. Conclusion: It seems that prolonged moderate-intensity aerobic training may be useful for middle-aged women by lifestyle changes aimed at proteins that affect bone density and prevent osteoporosis.